Development and validation of an instrument for the evaluation of HIV care in Primary Health Care - Clarissa Mourão Pinho; Morgana Cristina Leôncio de Lima; Mônica Alice Santos Silva; Cynthia Angélica Ramos de Oliveira Dourado; Regina Célia de Oliveira; Jael Maria de Aquino; Erika Simone Galvão Pinto; Maria Sandra Andrade (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To develop and validate an instrument to evaluate the decentralization process of care for People Living with HIV in Primary Health Care. Method: Methodological study, developed in four stages: elaboration of the logical model based on the triad Structure-Process-Outcomes; development of the instrument; content validation by expert judges and technical reviewers; and semantic validation. Online questionnaires were used, and the Kappa index was used for analysis. Results: The instrument with 68 items and 8 factors was submitted to validation by expert judges who recommended the exclusion of 3 items and the alteration of 2 factors. In the validation by technical reviewers, 2 items were excluded and 6 factors were highlighted; the agreement index was ≥0.75. In the semantic validation, 87.3% of the judges answered "totally agree" for the items presented. Conclusion: The instrument is validated for its content, has 63 items and has the potential to assess the care provided for people living with HIV in Primary Health Care.